Assessment of the attributes that most affect the choice of minced meat and hamburgers. (April 2023) - Cardona, María; Hernández, María; Fuentes, Ana; Barat, Jose M.; Fernández-Segovia, Isabel
Abstract: The objectives of this work were to identify the parameters that most influence Spanish consumers' choice of minced meat and hamburgers, and to determine the importance of different extrinsic attributes in meat products. A consumer survey was conducted by combining three methodologies: free listing task, rating the importance of different extrinsic attributes and a conjoint analysis. The free listing task showed that, of all the factors considered when selecting minced meat or hamburgers, price, expiration date, colour and appearance stood out. In the rating test, expiration date obtained the highest average score, followed by price and country of origin. The conjoint analysis showed consumers clearly preferred origin Spain, along with low price and the animal welfare label, which presented higher utility value than the sustainable packaging label. No presented label negatively impacted product choice. The information provided can be very useful for developing and marketing meat products that seek to meet today's consumer demands.